Trend Analysis of Revenue and Income from Rice Milling Busines in Wundulako District, Kolaka Regency - Nisah, Asma Nurun; Rianda, La; Abdullah, Sukmawati (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
ABSTRAKPenelitian ini bertujuan untuk mengetahui trend penerimaan dan pendapatan terhadap industri penggilingan padi PT. Griya Satria Mekongga di This study aims to determine the trend of acceptance and income of the rice mill business in Wundulako District, Kolaka Regency. The determination of the research location was carried out purposefully. Observation, interview, and documentation methods were used for data collection. The analytical method used is acceptance and income trend analysis. The results showed the trend towards acceptance and income of the rice mill business at PT. Griya Satria Mekongga in 2022-2026, namely increasing from year to year where in 2022 revenues amounted to IDR 6,408,084,400 and total costs amounted to IDR 5,248,425,170, so that revenues amounted to IDR 1,159,659,230 and in 2026 revenues amounted to Rp. 8,557,086,240 and a total cost of Rp. 5,248,425,170, so an income of Rp.3,308,661,070 is obtained.